Analisis Kualitas Pelayanan Poli Rawat Jalan tentang Standar Pelayanan Rumah Sakit di Rumah Sakit Mega Buana Palopo 2025 - Hasan, Amrullah; Uly, Nilawati; Sanuddin, Sudirman; Azwar, Muhammad (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
The quality of outpatient services is an essential indicator of hospital performance and patient satisfaction. At Mega Buana Hospital Palopo, patient complaints remain regarding waiting times, limited facilities, and staff communication, highlighting the need for evaluation based on the Ministry of Health Regulation No. 129/Menkes/SK/II/2008. This study aimed to analyze the relationship between human resources, medical staff interactions, service processes, and patient satisfaction with outpatient service quality. This research employed a quantitative design with a cross-sectional approach. A total of 116 patients were selected through accidental sampling. Data were collected using a validated and reliable questionnaire and analyzed using the chi-square test. The results revealed significant associations between human resources (p=0.001), medical staff interactions (p=0.003), and patient satisfaction (p=0.002) with outpatient service quality. The service process, particularly waiting time and queue management, proved to be important factors influencing patients’ perceptions of service quality. Overall, the service quality was categorized as good but not yet fully aligned with the national standards, especially in administrative speed, queue system, and facility comfort. In conclusion, outpatient service quality at Mega Buana Hospital Palopo is influenced by human resources, medical staff interactions, service processes, and patient satisfaction. The findings emphasize the importance of strengthening human resource management, improving the quality of medical staff communication, enhancing queue management, and providing adequate supporting facilities to meet national service standards.